Case Report: Septic arthritis in children caused by Streptococcus pyogenes–rational use of antibiotics - Yu, Dingle; Gao, Waiwai; Guo, Danchun; Lu, Qinghua; Chen, Yunsheng; Zheng, Yuejie; Wang, Wenjian; Yang, Yonghong (Frontiers in Cellular and Infection Microbiology, 2023)
To investigate the clinical characteristics and treatment of septic arthritis caused by Streptococcus pyogenes(S. pyogenes) in children, we retrospectively analyzed the clinical data, laboratory results, treatments and outcomes of three pediatric cases of septic arthritis caused by S. pyogenes occurring from 2016–2018. The three cases of septic arthritis included 1 boy and 2 girls, aged from 2–7 years. Two patients experienced fever, and in all three cases, the affected joints showed redness, swelling, an increased local skin temperature, tenderness and restricted limb movement. At the first visit, all three cases showed a significantly increased white blood cell count [(27.68–32.02)×109/mL] and a significantly increased erythrocyte sedimentation rate (113–134 mm/h). The C-reactive protein level was significantly increased in two cases (67 mg/L, 147.7 mg/L) and normal in one case. The procalcitonin level was normal in 1 case, elevated in 1 case, and undetected in 1 case. S. pyogenes isolated from cases 1 and 2 were emm1/ST28 and from case 3 was emm12/ST36. All patients were treated by abscess incision and drainage, and S. pyogenes was cultured in the abscess puncture fluid. All patients were treated with intravenous antibiotics after admission, and all patients were cured and discharged. The patients were followed up for 2 months, and their condition was improved and stable. No sequelae such as heart and kidney damage were detected. In conclusion, for children with septic arthritis, early diagnosis and timely treatment with incision and drainage followed by culture of the abscess puncture fluid are important. Once S. pyogenes infection is confirmed, β-lactam antibiotics provide effective treatment, avoiding use of broad-spectrum antibiotics.